2016
DOI: 10.1111/jam.13136
|View full text |Cite
|
Sign up to set email alerts
|

Nisin and lysostaphin activity against preformed biofilm of Staphylococcus aureus involved in bovine mastitis

Abstract: The action of lysostaphin, either alone or in combination with nisin, against established staphylococcal biofilm may represent an alternative to bovine mastitis control. However, the duration of the treatment should be considered for its application so that the best effectiveness can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 38 publications
(60 reference statements)
2
31
0
1
Order By: Relevance
“…These latter results also indicated that cell physiology (exponential versus stationary phase) has a significant impact on nisin susceptibility in S. aureus cultures. Taken together, these results agree with previous observations that demonstrated the differences in antimicrobial susceptibility between exponential versus stationary cells in different species of bacteria (37, 4951).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These latter results also indicated that cell physiology (exponential versus stationary phase) has a significant impact on nisin susceptibility in S. aureus cultures. Taken together, these results agree with previous observations that demonstrated the differences in antimicrobial susceptibility between exponential versus stationary cells in different species of bacteria (37, 4951).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that nisin inhibits both planktonic and sessile cells of Staphylococcus epidermidis and a MRSA clinical isolate (35, 36). However, although nisin is bactericidal against planktonic cultures, its inhibitory activity is often reduced against sessile cells (27, 37). Therefore, investigating the penetration of antimicrobials through bacterial biofilms could provide valuable information about their therapeutic potential and help to improve antimicrobial dosing regimens (20).…”
Section: Introductionmentioning
confidence: 99%
“…The combination elicited a reduction in MRSA CFU counts by 3 logs, whereas the individual antimicrobials were unable to decrease the CFU to such an extent (Dosler and Mataraci, 2013). A recent interesting study evaluated the activity of nisin and lysostaphin against pre-formed biofilms of S. aureus involved in bovine mastitis (Ceotto-Vigoder et al, 2016). After treatment for 24 h with a combination of nisin and lysostaphin, the biofilm pre-formed by all eight strains tested in the study was reduced by >50%, as suggested by biofilm detachment from the microtiter plates.…”
Section: Effects Of Antimicrobial Combinations Involving Bacteriocinsmentioning
confidence: 99%
“…After treatment for 24 h with a combination of nisin and lysostaphin, the biofilm pre-formed by all eight strains tested in the study was reduced by >50%, as suggested by biofilm detachment from the microtiter plates. Although no remarkable detachment could be noticed by confocal laser scanning microscopy (CLSM) analysis after a 4 h treatment, when the biofilm matrix of S. aureus 4181 was assayed for cell viability, most cells were shown to be dead (Ceotto-Vigoder et al, 2016). In contrast to the synergistic activity between nisin and lysostaphin, significantly higher concentrations of lysostaphin used on its own, up to 50-fold higher, were required to cause the same level of biofilm detachment achieved by nisin-lysostaphin combinations.…”
Section: Effects Of Antimicrobial Combinations Involving Bacteriocinsmentioning
confidence: 99%
“…Previously, this endopeptidase has been used to control targeted biofilms in several ways. The free form of Lst has been used by Ceotto-Vigoder et al (2016) against some S. aureus strains responsible for bovine mastitis. A high incidence of biofilm detachment and cell death in S. aureus 4181 was found after treating affected cells for 4 hr with 0.4 μg/mL of Lst.…”
Section: Metalloproteasesmentioning
confidence: 99%